Bitter, dry and popular - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Bitterleaf (Vernonia spp.) is, despite its common name, a very popular leafy vegetable, commonly found in Nigeria, Cameroon, Gabon and the Democratic Republic of Congo. Its rising popularity in and outside its region of origin, plus its scarcity...